Beyond self-defence: an examination of the legal basis for the unable or unwilling doctrine and its application in over-the-horizon operations in Afghanistan - Remerte, Ieva (Riga Graduate School of Law, 2023)
The Unable or Unwilling doctrine provides that a state that has been the target of a terrorist attack may resort to the use of force extraterritorially without attributing the conduct of the non-state actor nor obtaining the consent of the state from which the terrorist group operates. Despite various exercises of the doctrine by the United States, Russia, the United Kingdom, Turkey and Israel, the doctrine remains controversial as prior to the 9/11 terrorist attacks, the exercise of the doctrine based on a broad interpretation of Article 51 was generally condemned. Nevertheless, proponents of the doctrine have argued that the state practice and opinio juris have developed a custom or expanded the scope of Article 51. However, the United States, arguably the most vocal proponent of the doctrine being grounded on self-defence, in its latest exercise of the Unable or Unwilling doctrine in Over-the-Horizon operations in Afghanistan, did not claim the drone strike killing Ayman Al-Zawahiri, the Al-Qaeda leader, to be a measure of self-defence nor did the state provide any other legal basis. Thus the Thesis imposes the first research question- what is the legal basis for the Unable or Unwilling doctrine? By further exploring alternative reasonings, such as the plea of necessity and armed reprisals, the Thesis imposes a second research question- can the plea of necessity be invoked in Over-the Horizon operations in Afghanistan? The Thesis finds that the state practice of the doctrine and opinio juris is insufficient to establish a custom or expand the scope of Article 51. Whilst the plea of necessity does provide a potential legal basis for the doctrine and could have been invoked in Over-the-Horizon operations, uncertainties in the interpretation of Article 25 of ARISWA do not allow for a definitive answer. Thus, the Unable or Unwilling doctrine, if the plea of necessity cannot be invoked, remains unlawful as it constitutes an armed reprisal.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; self-defence; plea of necessity; Responsibility of States for Internationally Wrongful Acts